Effect of new punched vortex generators in a rectangular channel on heat transfer using Taguchi method. Issue 5 (29th July 2022) - Caliskan, S.; Dogan, A.; Sahin, U. R.
ABSTRACT: In this study, the effects of New Punched Rectangular Vortex Generators (NPRVGs) and Punched Rectangular Vortex Generators (PRVGs) inside a rectangular channel on heat transfer augmentation, Nusselt number, and friction factor were experimentally investigated. Temperature contours and average Nusselt numbers analyzed heat transfer characteristics resulting from the use of vortex generators. Furthermore, this study investigated the optimum values of the design parameters within the system of vortex generators by using the Taguchi method, and the orthogonal experimental plan was made for L16 (4 3 x2 1 ). Reynolds numbers (5181, 10363, 20328, 25510), winglet arrangement, winglet attack angles (15°, 30°, 45°, 75°) and a distance of punched winglet from the channel bottom (b) to constant winglet height (e = 25 mm) (b/e = 0.04, 0.12, 0.2 and 0.36) were determined the working parameters in the experiments. Measurements are carried out for a rectangular channel with aspect ratio AR = 2, winglet transverse pitch (S) to longitudinal winglet height (e) ratio of S/e = 0.67 and a winglet height (e) to channel height (H = 25 mm) ratio of e/H = 1. Heat transfer rates of NPRVGs and PRVGs were compared to the obtained results for a smooth channel. The heat transfer performance is improved considerably by the NPRVGs. The maximum thermal performance factor increased from 0.99 to 1.89 owing to the combination of the vortex generator and the newly punched hole.